2015
DOI: 10.1210/en.2015-1684
|View full text |Cite
|
Sign up to set email alerts
|

In the Heat of the Night: Thermo-TRPV Channels in the Salmonid Pineal Photoreceptors and Modulation of Melatonin Secretion

Abstract: Photoperiod plays an essential role in the synchronization of metabolism, physiology, and behavior to the cyclic variations of the environment. In vertebrates, information is relayed by the pineal cells and translated into the nocturnal production of melatonin. The duration of this signal corresponds to the duration of the night. In fish, the pinealocytes are true photoreceptors in which the amplitude of the nocturnal surge is modulated by temperature in a species-dependent manner. Thus, the daily and annual v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 52 publications
5
27
1
Order By: Relevance
“…Gu et 45 showed that green (532 nm) light activated TRPV1 expressed in Xenopus oocytes, but this activation did not occur with blue (406 nm) or with red (637 nm) light. Although TRPV channels are not yet generally accepted to be light-gated ion channels, a recent report suggests that thermosensitive TRPV1 and TRPV4 channels are expressed in the pineal photoreceptor cells of a teleost fish, where they modulate melatonin secretion in vitro 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Gu et 45 showed that green (532 nm) light activated TRPV1 expressed in Xenopus oocytes, but this activation did not occur with blue (406 nm) or with red (637 nm) light. Although TRPV channels are not yet generally accepted to be light-gated ion channels, a recent report suggests that thermosensitive TRPV1 and TRPV4 channels are expressed in the pineal photoreceptor cells of a teleost fish, where they modulate melatonin secretion in vitro 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological blockade of pinealocyte TRPV1 inhibited melatonin secretion. 124 Although the data linking thermo-TRP and biological rhythms are still scarce, and most of them were demonstrated in central clocks, valuable information has been provided to trace parallels between the role of thermo-TRP in central and peripheral synchronization, leading to necessary further investigation.…”
Section: The Role Of Trp Channels In Entrainment Of Peripheral Clocksmentioning
confidence: 99%
“…The water temperature induces changes of activity of the B-P-G axis and is considered as the most important environmental cue determining the timing of puberty in red spotted grouper. With recent reports on the receptors sensitive to light and WT, metabolism, physiology and behavior of diverse fish including zebrafish and rainbow trout [42][43][44] the mechanism correlating the WT-sensitive receptor and B-P-G axis should be investigated in future.…”
Section: Resultsmentioning
confidence: 99%